Analysis of Static Parameter Sensitivity of Independent Axle-bridge for Light Rail Train - Jiange LIU; Qiang LIU; Kunlan HUANG; Lizhong FAN; Jie WANG (机车电传动)
The axle-bridge is one of the key bearing components of the light rail train whose structural strength directly affects the safety of the train. The independent axle-bridge for a certain light rail train as the research object, was parametrically modeled to analyze the stress and deformation of the axle-bridge under different load conditions. The maximum equivalent stress and deformation was chosen as the objective function and the structure geometry size as a variable. Based on the response surface method (RSM), Latin hypercube sampling (LHS) was used to select a certain number of sample points for parameter sensitivity analysis. The results showed that the breath of axle head and thickness of flange significantly influenced deformation, as well as stress, in the selected parameters,providing a reference for the axle-bridge optimization design.